Factors Affecting the Performance of State Civil Servants at the Education and Culture Services of Kaur District - Hertedy Pratama; Oni Yulianti; Rinto Noviantoro (Penerbit Jurnal Indonesia, 2021)
The purpose of this research is to find out the factors that influence the performance of State Civil Apparatus employees at the Department of Education and Culture of Kaur Regency. This type of quantitative descriptive research, the sample is the entire population of State Civil Apparatus employees at the Education and Culture Office of Kaur Regency as many as 40 people with 28 male and 12 female compositions. The sampling method is by means of a census. The analytical tool used is multiple linear regression analysis using SPSS. analysis tools. The results of this study are the Individual Variable (X1) partially does not have a significant effect on the performance of State Civil Apparatus employees at the Department of Education and Culture of Kaur Regency with a tcount <t table (-1.406<2,024) or a significant value (0.168>0 0.05) and Psychological Variables (X2) partially have no significant effect on the performance of State Civil Apparatus employees at the Education and Culture Office of Kaur Regency with a value of tcount < t table (1,345 <2,024) or a significant value (0,187> 0.05). For the Organizational variable (X3) partially has a significant effect on the performance of State Civil Apparatus employees at the Department of Education and Culture of Kaur Regency with a value of tcount> t table (9.172> 2,024) or a significant value (0.000<0.05). However, simultaneously, Individual (X1), Psychological (X2) and Organizational (X3) variables together have a significant influence on the performance of State Civil Apparatus employees at the Education and Culture Office of Kaur Regency. F count > F table (31.068 > 2.45 ) or significant value (0.000<0.05).